Strategi Guru dalam Meningkatkan Minat Belajar Siswa pada Mata Pelajaran IPS di MI - Juliya Nur Hidayah; Salsabila Mutiara; Mutiara Tsani; Oman Farhurohman (STIT Muhammadiyah Bojonegoro, 2026)
The aim of this study is to examine various methods applied by teachers in elementary schools to increase students' interest in learning. This study uses a literature review approach, where data is collected from academic publications, scientific journals, and books that have undergone peer review to ensure that the information is reliable and valid. The lack of student interest in social studies subjects is often caused by teachers' inability to deliver the material, unvaried teaching methods, and students' perception of social studies as a confusing and boring subject. Research findings indicate that teachers play a crucial role in the teaching and learning process. Their roles include being a guide, classroom manager, facilitator, mediator, evaluator, and a source of inspiration for students. To increase students' interest in learning, teachers need to have a good understanding of the subject matter and it is very important to use innovative and interactive teaching strategies so that students can be more engaged and better understand the material.